The effect of neoadjuvant chemoradiotherapy on whole-body physical fitness and skeletal muscle mitochondrial oxidative phosphorylation in vivo in locally advanced rectal cancer patients--an observational pilot study. - Malcolm A West; Lisa Loughney; Daniel Lythgoe; Christopher P Barben; Valerie L Adams; William E Bimson; Michael P W Grocott; Sandy Jack; Graham J Kemp (PLoS ONE)
Background In the United Kingdom, patients with locally advanced rectal cancer routinely receive neoadjuvant chemoradiotherapy. However, the effects of this on physical fitness are unclear. This pilot study is aimed to investigate the effect of neoadjuvant chemoradiotherapy on objectively measured in vivo muscle mitochondrial function and whole-body physical fitness. Methods We prospectively studied 12 patients with rectal cancer who completed standardized neoadjuvant chemoradiotherapy, recruited from a large tertiary cancer centre, between October 2012 and July 2013. All patients underwent a cardiopulmonary exercise test and a phosphorus magnetic resonance spectroscopy quadriceps muscle exercise-recovery study before and after neoadjuvant chemoradiotherapy. Data were analysed and reported blind to patient identity and clinical course. Primary variables of interest were the two physical fitness measures; oxygen uptake at estimated anaerobic threshold and oxygen uptake at Peak exercise (ml.kg-1.min-1), and the post-exercise phosphocreatine recovery rate constant (min-1), a measure of muscle mitochondrial capacity in vivo. Results Median age was 67 years (IQR 64-75). Differences (95%CI) in all three primary variables were significantly negative post-NACRT: Oxygen uptake at estimated anaerobic threshold -2.4 ml.kg-1.min-1 (-3.8, -0.9), p = 0.004; Oxygen uptake at Peak -4.0 ml.kg-1.min-1 (-6.8, -1.1), p = 0.011; and post-exercise phosphocreatine recovery rate constant -0.34 min-1 (-0.51, -0.17), p<0.001. Conclusion The significant decrease in both whole-body physical fitness and in vivo muscle mitochondrial function raises the possibility that muscle mitochondrial mechanisms, no doubt multifactorial, may be important in deterioration of physical fitness following neoadjuvant chemoradiotherapy. This may have implications for targeted interventions to improve physical fitness pre-surgery. Trial registration Clinicaltrials.gov registration NCT01859442.